Kontribusi Minat, Motivasi, Perkembangan Teknologi Terhadap Kreativitas Siswa Dalam Pembelajaran Seni Budaya Di SMA N 1 Pulokulon - Sudarwahyuni, Rita; , Prof. Dr. Sutama,M.Pd; , Dr. Suyatmin, M.Si (2017)
This study aims to: (1) To examine the contribution of interest, motivation, development of technology for the creativity of students in arts and culture in SMA N 1 Pulokulon. (2) To examine the contribution of interest in the creativity of students in arts and culture in SMA N 1 Pulokulon. (3) For examine contribution of motivation for the creativity of students in arts and culture in SMA N 1 Pulokulon. (4) To examine the contribution of technology to the development of creativity of students in arts and culture in SMA N 1 Pulokulon, This research uses quantitative methods, this study was conducted in SMA N 1 Pulokulon. The results of the study : (1) There is a positive contribution to students' interest towards the creativity of students at SMA Negeri 1 Pulokulon. With efective contribution to the creativity of the students interest in students at SMA Negeri 1 Pulokulon by 24.5% and the relative contribution of 31.8%. (2) There is a positive contribution to student motivation for the creativity of students at SMA Negeri 1 Pulokulon. With effective contribution to the creativity of student motivation of students in SMA Negeri 1 Pulokulon of 21.3% and the relative contribution of 27.6%. (3) There is a positive contribution to the technological development of student creativity at SMA Negeri 1 Pulokulon..With effective contribution of technology to the development of creativity of students at SMA Negeri 1 Pulokulon 31.3% and the relative contribution of 46.6%. (4) There is a positive contribution interest, motivation and development of technology for the creativity of students at SMA Negeri 1 Pulokulon. With effective contribution of independent variables of interest, motivation and development of technology simultaneously to the creativity of students and the remaining 77.1% is influenced by other variables not included in this study.